Dissecting the Trajectories of Food Insecurity in Katsina State 1999-2023 - Bappah , Fatima; Adejoh, Sunday (Kashere Journal of Politics and International Relations, 2025)
Food shortage has been a big problem in Katsina State, Nigeria, for many years. This study examines the nature of food insecurity in Katsina State from 1999 to 2023. The study adopts the Human Security Theory as its theoretic framework of analysis. This study adopts the qualitative research method and data for the study were obtained from secondary sources such as; government reports, books, journals and of course the internet was utilized. The research examines different factors, such as climate change, weak government policies, and security issues, have made it hard for people to get enough food. As a result, people have had to depend more on food brought from outside the state and on help from aid organisations. The study also examines government efforts like the Agricultural Transformation Agenda (ATA) and the Anchor Borrowers' Program (ABP) to see if they have helped improve food production and supply. Findings show that while the government and other organisations have tried to improve food availability, problems like bad roads, lack of financial support for farmers, and poor market systems have slowed the progress. The research also highlights the role of international organisations in providing food aid and training for farmers. In conclusion, this study suggests that solving food insecurity in Katsina State requires that the government and communities need to work together to improve security, support farmers, and find better ways to deal with climate change, insecurity etc.